PENERAPAN BEE COLONY OPTIMIZATION ALGORITHM UNTUK PENENTUAN RUTE TERPENDEK (Studi Kasus : Objek Wisata Daerah Istimewa Yogyakarta) - , DANURI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The shortest path determination is an optimization problem which often used as a case study for research. Distance is the most defining factor in performing the search paths to be passed. Path with the shortest distance would be chosen as a path selection. Bee colony optimization algorithm used in this research to complete problems the shortest path determination for multi destination with developing of exhaustive search. Local search using forward and backward. The value probability of a path is base in transition process and duration of waggle dance every bee who had found the position of the goal will be a preferred route. The preferred route of each alternative route will be compared to find the shortest alternative route. The results obtained in this research is bee colony optimization algorithm can be used to find the shortest path to the multi destination. The number of bees are removed greatly affects in finding routes that can be passed. The more the number of bees that removed the greater the chances of finding the shortest route.